Bee keeping: A profitable venture - Chahal, Pardeep; Verma, Tarun; Malik, Anil Kumar; Sheoran, R S; Hudda, R S; Rohilla, P P; Singh, S K (Indian Farming, 2019)
Rearing of honey bees is called Apiculture. Keeping bees at a large scale for commercial purpose as a business plan is increasing in this fast growing world. Apiculture business need less investment but it require labours with great care. It is hard to keep bees as the business if proper knowledge about apiculture is not there as bees are wild in nature. One can easily learn apiculture and can earn more money as profit able enterprise with less effort.